Sostenibilidad de una empresa constructora pyme en Colombia (2018)
This document collects the shortcomings of Pymes construction companies that do not allow it to be sustainable over time; and based on numbers of the different studies and on literature of the theoretical framework, strategies are proposed that serve in the management decision-making processes that cover aspects such as the environment, competition, the global economy, and that Once, supported by the competitive advantages that can be had within the organization, it allows the construction companies to be sustainable over time.